Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

The reproductive ecology of Loligo squids (Cephalopoda: Myopsida) in Lusitanian zoogeographical province - Vladimir Laptikhovsky; Ana Moreno; Daniel Oesterwind; Catalina Perales-Raya; Graham Pierce; Jean-Paul Robin; Ignacio Sobrino; Maria Valls; Roger Villanueva; Athena Allen; Esther Abad; Giambattista Bello; et al. (Regional Studies in Marine Science, 2025)

The power of hydropeaking: Trade-offs between flexible hydropower and river ecosystem services in Europe - Terese E. Venus; Oreoluwa Ola; Maria Alp; Nico Bätz; Maria Dolores Bejarano; Isabel Boavida; Maria Cristina Bruno; Roser Casas-Mulet; Mauro Carolli; Gabriele Chiogna; Marie-Pierre Gosselin; Jo H. Halleraker; et al. (Ecological Economics, 2025)

Riparian habitat connectivity restoration in an anthropized landscape: A multi-species approach based on landscape graph and soil bioengineering structures - Etienne Boncourt; Laurent Bergès; Maria Alp; Blandine Dupont; Timothée Herviault; André Evette (Environmental Management, 2024)

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

Getting from Sea to Nurseries: Considering Tidal Dynamics of Juvenile Habitat Distribution and Connectivity in a Highly Modified Estuarine Riverscape - Maria Alp; Céline Le Pichon (Ecosystems, 2021)

Nebulization of antimicrobial agents in mechanically ventilated adults in 2017: an international cross-sectional survey - Joana Alves; Emine Alp; Despoina Koulenti; Zhongheng Zhang; Stephan Ehrmann; Stijn Blot; Matteo Bassetti; Andrew Conway-Morris; Rosa Reina; Enrique Teran; Candela Sole-Lleonart; Maria Ruiz-Rodríguez; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Erratum to: The deep-water squid Octopoteuthis sicula Rüppell, 1844(Cephalopoda: Octopoteuthidae) as the single species of the genus occurring in the Mediterranean Sea - Patrizia Jereb; Rita Cannas; Porzia Maiorano; Giambattista Bello; Fulvio Garibaldi; Marco Mereu; Francesco G. Ancona; Giovanni Ammendolia; Pietro Battaglia; Önder Duysak; Hendrik Jan T. Hoving; Eugenia Lefkaditou; et al. (Marine Biology, 2016)

Phenological response of a key ecosystem function to biological invasion - Maria Alp; Julien Cucherousset; Mathieu Buoro; Antoine Lecerf (Ecology Letters, 2016)
Although climate warming has been widely demonstrated to induce shifts in the timing of many biological events, the phenological consequences of other prominent global change drivers remain largely unknown. Here, we investigated the effects of biological invasions on the seasonality of leaf litter decomposition, a crucial freshwater ecosystem function. Decomposition rates were quantified in 18 temperate shallow lakes distributed along a gradient of crayfish invasion and a temperature‐based model was constructed to predict yearly patterns of decomposition. We found that, through direct detritus consumption, omnivorous invasive crayfish accelerated decomposition rates up to fivefold in spring, enhancing temperature dependence of the process and shortening the period of major detritus availability in the ecosystem by up to 39 days (95% CI : 15–61). The fact that our estimates are an order of magnitude higher than any previously reported climate‐driven phenological shifts indicates that some powerful drivers of phenological change have been largely overlooked.

Ecological thresholds and riparian wetlands: an overview for environmental managers - Stefano Larsen; Maria Alp (Limnology, 2015)

Shifts in isotopic signatures of animals with complex life-cycles can complicate conclusions on cross-boundary trophic links - Maria Alp; Barbara L. Peckarsky; Stefano M. Bernasconi; Christopher T. Robinson (Aquatic Sciences, 2013)

The hydro-morphological index of diversity: a tool for describing habitat heterogeneity in river engineering projects - Walter Gostner; Maria Alp; Anton J. Schleiss; Christopher T. Robinson (Hydrobiologia, 2013)